Vsebnost skatola v maščobnem tkivu merjascev določena s spektrofotometrično metodo - Žemva, Marjeta (Acta agriculturae Slovenica, 2012)
Due to tendency for banning surgical castration of boars, alternatives such as fattening of boars for human consumption are being considered. Primary problem in boar`s meat consumption is boar`s taint, which is to a large extent the result of skatole (3-methyl indole) content. Spectrophotometric method for determination of skatole in fat tissue was introduced. Samples from three genotypes of boars from five different breedings, aged between 101 and 310 days were collected. When introducing the method, the first group of samples was analyzed, the samples that were obtained later represented a second group. Introduced method is repeatable (coefficient of variability, CV = 13.6), reproducible (CV = 21.3) and has good recovery (96%). Skatole contentin boar's back fat in first group was between 0.01 to 0.62 ppm, on average 0.23 ppm. The second group contained on average 0.71 ppm skatol (between 0.07 and 1.26 ppm). Effect of genotype, breeder and age on skatole content was not found.
Keywords: pigs; prašiči; boars; merjasci; back fat; hrbtno maščobno tkivo; skatol; spectrofotometric method; spektrofometrična metoda